2020
DOI: 10.18502/ijph.v48i7.2958
|View full text |Cite
|
Sign up to set email alerts
|

Augmented cAMP Signaling by Co-Administration of Resvera-trol and Curcumin: A Cellular Biosensor Kinetic Assessment

Abstract: Background: Curcumin and resveratrol are two polyphenolic compounds extensively investigated for their medicinal effects on inflammatory signaling. However, there is a paucity of information on the Adenosine-3’, 5’-cyclic monophosphate (cAMP) kinetics following administration of curcumin and resveratrol in biological systems. In this study, kinetic modulation of cAMP as a target detection messenger in pro-inflammatory pathways was assessed by co-administration of curcumin and resveratrol using a cellular senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…High levels of cAMP, which maintains oocytes in a meiotic arrested state within follicular. Importantly, there exists reciprocal relationship between cAMP and SIRT1, whereby cAMP enhances SIRT1 signaling, While SIRT1 ensures the maintenance of high cAMP levels 141 , 142 .…”
Section: Srt2104 In Female Reproductive System Diseasesmentioning
confidence: 99%
“…High levels of cAMP, which maintains oocytes in a meiotic arrested state within follicular. Importantly, there exists reciprocal relationship between cAMP and SIRT1, whereby cAMP enhances SIRT1 signaling, While SIRT1 ensures the maintenance of high cAMP levels 141 , 142 .…”
Section: Srt2104 In Female Reproductive System Diseasesmentioning
confidence: 99%
“…In the arteriovenous shunt model, salvianolic acid A significantly inhibited the activation and aggregation of platelets stimulated by various agonists, and its underlying mechanism may involve the induction of cAMP [ 45 ]. Similarly, dimethyl fumarate, resveratrol, and curcumin have been shown to regulate cAMP levels [ 46 , 47 ].…”
Section: The Mechanisms Underlying the Antiplatelet Effect Of Pbcrbscmmentioning
confidence: 99%
“…In addition, it is reported the involvement of endoplasmic reticulum-stress in curcumin-dependent apoptosis of HL-60 cells [ 142 ] and the induction of unfolded protein response (UPR) components promoting apoptosis after the curcumin treatment in activated human CD4 + T cells promoting apoptosis [ 140 ]. It is also observed that, with the treatment of HEK-293T cells at 10 µM concentration, curcumin upregulated cAMP signaling [ 143 ].…”
Section: The Camp Signalling In the Regulation Of Mitochondrial Acmentioning
confidence: 99%